The map of consciousness explained : a proven energy scale to actualize your ultimate potential - Hawkins, David R., 1927- (Hay House, Inc., 2020)
"The Map of Consciousness Explained is an essential primer on the late Dr. David R. Hawkins's teachings on human consciousness and their associated energy fields. Using muscle testing, Dr. Hawkins conducted more than 250,000 calibrations during 20 years of research to define a range of values, attitudes, and emotions that correspond to levels of consciousness. This range of values-along with a logarithmic scale of 1 to 1,000-became the Map of Consciousness, which Dr. Hawkins first wrote about in his New York Times bestseller, Power vs. Force. In this book, readers will gain an introduction and deeper understanding of the Map, with visual charts and practical applications to help them heal, recover, and evolve to higher levels of consciousness and energy"--